Pendekatan Struktural Dalam Menganalisis Drama Kereta Kencana Karya WS Rendra - M. Nur Kholis; Akhmad Fatoni (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
Literature serves as a mirror reflecting the social and cultural dynamics of society. This serves as the foundation for analyzing the play "Kereta Kencana" in this journal. The work of W.S. Rendra is the subject of this study, aimed at uncovering its meaning and structure through a structuralist approach. This research delves into various narrative layers, structures, and messages contained within the text. Utilizing a qualitative descriptive method and a structuralist approach, the case study on "Kereta Kencana" will analyze its intrinsic elements. The findings provide a deeper understanding of intrinsic components such as characters, characterization, plot, setting, point of view, moral, and theme. Additionally, this study explores the relationships between characters, plot development, philosophical and social messages, as well as the stylistic choices employed.